HSP110 as a Diagnostic but Not a Prognostic Biomarker in Colorectal Cancer With Microsatellite Instability - Tachon, Gaelle; Chong-Si-Tsaon, Arnaud; Lecomte, Thierry; Junca, Audelaure; Frouin, Éric; Miquelestorena-Standley, Elodie; Godet, Julie; Evrard, Camille; Randrian, Violaine; Chautard, Romain; Auriault, Marie-Luce; Moulin, Valérie; et al. (Frontiers in Genetics, 2022)
Determination of microsatellite instability (MSI) using molecular test and deficient mismatch repair (dMMR) using immunohistochemistry (IHC) has major implications on colorectal cancer (CRC) management. HSP110 T17 microsatellite has been reported to be more monomorphic than the common markers used for MSI determination. Large deletion of HSP110 T17 has been associated with efficacy of adjuvant chemotherapy in dMMR/MSI CRCs. The aim of this study was to evaluate the interest of HSP110 deletion/expression as a diagnostic tool of dMMR/MSI CRCs and a predictive tool of adjuvant chemotherapy efficacy. All patients with MSI CRC classified by molecular testing were included in this multicenter prospective cohort (n=381). IHC of the 4 MMR proteins was carried out. HSP110 expression was carried out by IHC (n=343) and the size of HSP110 T17 deletion was determined by PCR (n=327). In the 293 MSI CRCs with both tests, a strong correlation was found between the expression of HSP110 protein and the size of HSP110 T17 deletion. Only 5.8% of MSI CRCs had no HSP110 T17 deletion (n=19/327). HSP110 T17 deletion helped to re-classify 4 of the 9 pMMR/MSI discordance cases as pMMR/MSS cases. We did not observe any correlation between HSP110 expression or HSP110 T17 deletion size with time to recurrence in patients with stage II and III CRC, treated with or without adjuvant chemotherapy. HSP110 is neither a robust prognosis marker nor a predictor tool of adjuvant chemotherapy efficacy in dMMR/MSI CRC. However, HSP110 T17 is an interesting marker, which may be combined with the other pentaplex markers, to identify discordant cases between MMR IHC and MSI.